Patient autonomy - lbugami, Muneerah; El Alem, Usamah (International Journal of Medicine, 2021)
Patient autonomy is one of the most important ethical values in the health care practice. Patientsâ€™ autonomy means the right of patients to make decisions about their medical care without their health care provider trying to influence the decision. Patientsâ€™ autonomy allows health care providers to educate the patients but do not allow them to make the decision for the patients.Â Â